11 Arrhythmogenic Right Ventricular Cardiomyopathy-Like Phenotype Induced by Endurance Training and Prevented by Preload Reduction in Heterozygeous Desmoglein-2 Mutants. (19th January 2014) - Fabritz, L; Fortmueller, L; Vloumidi, E; Sakhtivel, S; Syeda, F; Leube, R; Kirchhof, P; Krusche, C
Abstract : Arrhythmogenic right ventricular cardiomyopathy (ARVC) significantly contributes to sudden cardiac death in young otherwise healthy patients, especially endurance athletes. 5–10% of patients with ARVC harbour mutations in the extracellular domains of the desmoglein (DSG) 2 gene. To assess the role of DSG2 in ARVC pathomechanism, mice lacking exons 4–6 of the endogenous DSG2 gene (DSG2mt) were generated. Homozygous DSG2mt/mice developed dilatation of ventricles and pronounced fibrosis. Heterozygous DSG2mt/wt mutants did not show such morphological alterations. Methods: To study whether exercise provokes a cardiac phenotype in DGSwt/mt mice, they were subjected to endurance training and compared with wild-type (WT) littermates. We also studied if preload reduction can prevent right ventricular dilation with training by concomitant therapy with nitrates and diuretics. Echocardiography was performed with 2% isoflurane + oxygen, using a small animal ultrasound unit. Right ventricular (RV) dimensions were increased in DSG2wt/mt after training compared to pre-training and compared to WT after training. Electrophysiological studies in isolated Langendorff DSGwt/mt and WT hearts from mice terminally anaesthetised with urethane (2 mg/kg) showed a correlation of the DSG2 mutation with increased arrhythmia inducibility after endurance training. Ventricular arrhythmias were induced by a single extra stimulus during right ventricular stimulation in 5 of 8 DSG2wt/mt, but in none of the 7 WT hearts (p = 0.03). Preload reduction prevented excessive right ventricular enlargement with endurance training in DSG2wt/mt. In conclusion, endurance training revealed an ARVC-like phenotype in heterozygous desmoglein mutant mice. Right ventricular dilation could be prevented by preload-reducing therapy.